Association between lifetime alcohol consumption and prostate cancer risk: A case-control study in Montreal, Canada. (December 2016) - Demoury, Claire; Karakiewicz, Pierre; Parent, Marie-Elise
Highlights: Population-based case-control study, including nearly 4000 subjects. Information on disease aggressiveness. Excess risk of high-grade cancer with high intake of alcohol, especially beer. Associations were stronger among current drinkers. Results were influenced by prostate cancer screening history. Abstract: Background: Alcohol intake may increase the risk of prostate cancer (PCa). Many previous studies harbored important methodological limitations. Methods: We conducted a population-based case-control study of PCa comprising 1933 cases and 1994 controls in Montreal, Canada. Lifetime alcohol consumption was elicited, by type of beverage, during in-person interviews. Odds ratios (OR) and 95% confidence intervals (CI) assessed the association between alcohol intake and PCa risk, adjusting for potential confounders and considering the subjects' PCa screening history. Results: We observed a weak, non-significant positive association between high consumption of total alcohol over the lifetime and risk of high-grade PCa (OR = 1.18, 95% CI 0.81–1.73). Risk estimates were more pronounced among current drinkers (OR = 1.40, 95%CI 1.00–1.97), particularly after adjusting for the timing of last PCa screening (OR = 1.52, 95%CI 1.07–2.16). These associations were largely driven by beer consumption. The OR for high-grade PCa associated with high beer intake was 1.37 (95%CI 1.00–1.89); it was 1.49 (95%CI 0.99–2.23) among current drinkers and 1.68 (95% CI 1.10–2.57) after adjusting for screening recency. High cumulative consumption of spirits was associated with a lower risk of low-grade PCa (OR = 0.75, 95%CI 0.60–0.94) but the risk estimate no longer achieved statistical significance when restricting to current users. No association was found for wine consumption. Conclusion: Findings add to the accumulating evidence that high alcohol consumption increases the risk of high-grade PCa. This association largely reflected beer intake in our population, and was strengthened when taking into account PCa screening history.